Parent experiences and psychosocial support needs 6 months following paediatric critical injury: A qualitative study. Issue 5 (May 2019) - Foster, Kim; Mitchell, Rebecca; Young, Alexandra; Van, Connie; Curtis, Kate
Highlights: Parents and families experienced substantial emotional impacts 6 months following child injury. Parents received no psychosocial follow-up from the hospital and limited information about community services. Family-centred continuity-of-care approach is needed from acute injury to post-discharge recovery. Abstract: Introduction: Parents of critically injured children can experience high levels of psychological distress post-injury, however little is known about their experiences and needs following injury. This study aimed to explore parent experiences and psychosocial support needs in the six months following child critical injury. Methods: An interpretive qualitative design was used. Semi-structured interviews were conducted with 30 parents of 23 critically injured children. Interviews explored parent experiences and psychosocial support needs. Qualitative data were managed using NVIVO 10 and analysed thematically. Results: Four themes were identified: integrating back into home life; adjusting mentally and emotionally to injury; coping with injury as a family; and navigating resources to meet family needs. Parents and families experienced substantial ongoing emotional impacts at 6 months following child injury. Parents were unprepared for the negative changes in their child's psychological wellbeing and behaviour post injury, and parents' mental health was negatively impacted, with mothers more likely to seek emotional support than fathers. Parents reported receiving no psychosocial follow-up from the hospital and limited information about community services and accessing local community resources on returning home. Conclusions: There is a need to include all family members in discharge planning, and to use a family-centred continuity-of-care approach from the time of child injury through to post-discharge recovery. To strengthen parent and family wellbeing, a biopsychosocial holistic approach is recommended, including cognitive-behavioural and other psychological strategies to help reduce distress for parents and all family members and strengthen their coping capacity. A dedicated family support coordinator role to facilitate care over the child recovery trajectory, and development of accessible online and e-psychosocial support resources for parents and families are recommended.